The Effect of Corporate Social Responsibility Disclosures and Good Corporate Governance Mechanism on Company Value - Reinaldi Putra Tappang, Anugerah; Ery Setiawan, Putu (Muhasabatuna : Jurnal Akuntansi Syariah, 2024)
Company value is important because it can influence investors' interest in making investment decisions in a company. Companies that have good corporate governance, good performance and responsibility for the social environment will make investors confident about the shares invested in the company. The higher the company value, the more prosperous the company's shareholders will be. The aim of this research is to obtain empirical evidence of the influence of disclosure of corporate social responsibility and good corporate governance mechanisms on company value. This research is quantitative research using secondary data obtained from financial reports and annual reports on manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for the 2019-2022 period. The sampling technique used purposive sampling technique which selected 22 sample companies that met the specified criteria. Testing this hypothesis uses multiple linear regression analysis with the help of the SPSS program. The research results show that corporate social responsibility, the board of commissioners, have a positive effect on company value, while the board of directors, audit committee, constitutional ownership and managerial ownership have a negative effect on company value.